COMPARATIVE ANALYSIS OF THE CHRONIC TOXICITY OF THE INGAVIRIN, RIMANTADINE, TRIAZAVIRIN, AND MOXIFLOXACIN DRUGS - Ivanovna Reshetnikova, Tatiana; Sergeyevich Zenkin, Alexander (Revista Inclusiones, 2020)
The authors have aimed at comparing the new Triazavirin antiviral drug with already proven ones, such as Ingavirin and Rimantadine. Moxifloxacin, 4th generation fluoroquinolone, was used as antibacterial drugs. Outbred white mice were used as laboratory animals. During the experiment, one control and four experimental groups were formed based on analogues, five females and five males in each. The drugs were administered to the mice intragastrically, using a probe, previously diluted in 0.2 ml of saline. The drugs were administered to the experimental mice once a day, for 21 days. Slaughter by decapitation took place on day 22, and blood was drawn for laboratory tests. During the trial use of Ingavirin, Rimantadine, Triazavirin, and Moxifloxacin in recommended doses in laboratory animals (outbred mice), the Triazavirin drug has positively proved itself. Triazavirin is safe and does not cause changes in white and red blood cells. When using Triazavirin, biochemical blood parameters are within the species physiological range. The ALT and ALP level decreases, and cholesterol corresponds to the control.